Bodies in blue : disability in the Civil War north - Handley-Cousins, Sarah, 1984- (Uncivil wars., 2019)
"Disabled soldiers and veterans occupied a difficult space in the Civil War North. The realities of living with a disability were ever at odds with the expectations of manhood. Disability made it difficult for soldiers to adhere to the particular masculine standards of the Union Army, yet when soldiers were able to control their bodies in order to fit manly ideals, they were met with suspicion when they requested accommodation or support. The very definition of masculine disability was ever in dispute as soldiers, physicians, lawmakers, bureaucrats and civilians each questioned what made a war wound authentic. Further, they each pondered what role disabled soldiers should play, whether in the course of war, in the progression of medicine, or in Gilded Age politics. It is in this tension, between the demands of masculinity and the realities of disability, that we can see the murkier undercurrent of the history of disabled Civil War veterans: that even when surrounded by the triumphant cheers and sentimental sighs that praised war wounds as patriotic sacrifices, disabled Union veterans faced enormous difficulty as they negotiated a life spent walking the fine line between manliness and emasculation. Sarah Handley-Cousins's manuscript makes an important contribution to the burgeoning field of the Civil War veteran experience, Civil War medicine, masculinity, and the soldier transition to civilian life. She breaks new ground with her focus on invisible wounds, as most scholars have concentrated on amputees"--